Greenwich Park - Faulkner, Katherine (Gallery Books, 2022)
"A sophisticated female-led thriller about a woman whose life starts to unravel as a result of her friendship with an unpredictable single mother, Greenwich Park explores the terrible consequences of guilt, the complexity of female friendships, and the fallibility of the memories we cherish"--